Sistem Penunjang Keputusan Pemilihan Pelanggan Prioritas Dengan Metode SAW Pada PT. Tixpro Informatika Megah - Putri Natasa; Bima Cahya Putra; Atik Ariesta; Yuliazmi Yuliazmi (Jurnal Ticom: Technology of Information and Communication, 2023)
PT. Tixpro Informatika Megah is a trading company that focuses on Information Technology (IT) products, which have problems with the product distribution process, because there are several limited products, which are caused by product deliveries from unpredictable suppliers. So this research proposes to implement a decision support system (DSS) application for selecting priority customers using the Simple Additive Weighting (SAW) method, with the aim of obtaining selected customers as priorities in product distribution and the selected customers getting 50 grams of metal gold. The criteria that will be used in the DSS application are total purchases, payment accuracy, number of transactions (per month), delivery distance, credit limit value, and length of subscription. In designing the DSS application, the programming language used is PHP, the database uses PhpMyAdmin, and the framework used is bootstrap. The conclusion of this study is that the DSS application for selecting priority customers using the SAW method can help users (admins) in making decisions about priority customers who are selected to be prioritized in distribution, because they have been selected with established limits such as criteria, sub-criteria, and weights. As well as with the validation module, the report team head who will be the determinant of final decision-making can make a priority customer order which according to him is better, as well as the module for printing validation reports and printing calculation reports can be given to leaders, as well as attachments that will be used by the head of warehouse for used as a reference in the distribution of products.